glsim: A general library for numerical simulation - Grigera, Tomás Sebastián (2011)
We describe glsim, a C++ library designed to provide routines to perform basic housekeeping tasks common to a very wide range of simulation programs, such as reading simulation parameters or reading and writing self-describing binary files with simulation data. The design also provides a framework to add features to the library while preserving its structure and interfaces.